The Impact of Noyyal River Basin on the Quality of Ground Water in Tiruppur District - A Study - Ravichandran, K.; R. Sundararajan, Dr.; N. Balasundaram, Dr.; T. Senthil Vadivel, Dr. (International Journal of Engineering and Technology, 2018)
The textile dyeing units operating in Tiruppur have provided Zero Liquid Discharge (ZLD) plants and the system has been in operation for the past ten years. Data on the quality of ground and surface water available with various government agencies such as Public Works Department, Tamil Nadu Pollution Control Board and Central Ground Water Board for the past ten years were collected for the study. Visual MODFLOW, a mathematical Model was used as a tool in the study for analysing the migration of contaminants in the ground water. The parameter, Total Dissolved solids (TDS) was used to represent the contamination level in the ground water. The study area, covering the cluster of industries upstream and downstream of Tiruppur Corporation was selected, and using the data for the period from 2008 to 2017, the Model was validated. The validated Model was used to make prediction of ground water quality for the next ten years under different scenario.Â Â